Activity Of The Commission For Aid To The Hungry Population Evacuated To Turkestan (Texas Journal of Multidisciplinary Studies, 2025)
This article describes the evacuation of the starving population of the famine-stricken regions of Russia to the Turkestan ASSR in the 1920s and their accommodation, food, clothing and other supplies. It also discusses the assistance provided by the state to the starving evacuated to our country and the kindness shown by the generous Turkestan population to the resettled peoples, as well as the reasons and processes of the Soviet government's evacuation of the starving to Turkestan based on archival materials and scientific literature, and provides an objective solution